Colocasia esculenta stems for the isolation of cellulose nanofibers: a chlorine-free method for the biomass conversion - Dominic, C. D. Midhun; Maheswary, S.; Neenu, V. K.; Sajadi, S. Mohammad; Rosa, Derval dos Santos; Begum, P. M. Sabura; Mathew, Mariya; Ajithkumar, T. G.; Parameswaranpillai, Jyotishkumar; George, Tresa Sunitha; Resmi, V. C.; Ilyas, R. A.; et al. (Biomass Conversion and Biorefinery, 2024)
The reuse of waste products is the green key to sustainability. The extraction of cellulose nanofibers from Colocasia esculenta stems is presented in the paper. The study proved that the waste biomass could be effectively re-engineered into highly valued cellulose nanofibers (CNFs). Cellulose nanofibers were extracted via a chemo-mechanical route. The pre-treatments included mild alkali hydrolysis (2% NaOH) and chlorine-free bleaching (peroxide bleaching in an alkaline medium). Cellulose I-beta structure was confirmed using C-13 solid-state nuclear magnetic resonance spectroscopy and X-ray diffraction analysis. The elemental analysis of CNFs detected the elements, carbon and oxygen. The CNFs had a crystallinity and transmittance of 71.72% and 60%, respectively. Microscopic studies verified the elimination of non-cellulosic components and the fibrous nature of CNFs. Moreover, the fiber diameter of CNFs was 20-40 nm. Thermal analysis revealed good thermal stability of 335.8 degrees C (T-50) for nanofibers. Long-term aids are numerous in eco-friendly technology. Developing an eco-design will support zero waste ideals, lowers carbon dioxide emissions, and encourages a circular economy. Owing to the merits of natural fibers, they can be adopted in various sectors including packaging, automobile, aerospace, electronics, biomedical, construction, and furniture.
Keywords: acid hydrolysis; cellulose nanofibers; Colocasia esculenta stems; High crystallinity

Green engineering of cellulose nanofibers and nanopapers from Wodyetia bifurcata fruits: a sustainable approach with emphasis on process optimization and tensile property assessment - Sankar, Sameera; Neenu, K. V.; Parameswaranpillai, Jyotishkumar; Ajithkumar, T. G.; Shelke, Ankita Ramesh; Begum, P. M. Sabura; Bipinbal, P. K.; George, Tresa Sunitha; Badawi, Michael; Dominic, Midhun (Biomass Conversion and Biorefinery, 2025)
Nanocellulose emerges as a highly promising material with versatile applications, offering solutions to environmental and sustainability challenges. This study delves into the extraction of cellulose nanofibers (CNFs) from Wodyetia bifurcata fruit pulp through mild oxalic acid hydrolysis assisted by steam explosion. To ensure environmental compatibility, chlorine-free pre-treatments were applied to eliminate non-cellulosic components. Chemical composition analysis verified the effective removal of non-cellulosic elements, validated by Fourier transform infrared spectroscopy (FTIR). Solid-state 13C nuclear magnetic resonance (13C NMR) spectroscopy confirmed the presence of type I cellulose α-polymorph in the CNF, while a crystallinity index of 60% was determined by X-ray diffraction analysis (XRD). The transmission electron microscopy (TEM) images revealed a fibrous morphology with a fiber diameter ranging from 9 to 36 nm. Dynamic light scattering (DLS) was employed to corroborate the observed fiber diameter. Mild acid hydrolysis elevated the maximum degradation temperature (Tmax) of CNF to 39 °C compared to the pristine sample. Furthermore, this research explores the application of CNFs in nanopaper development using a casting method. The resulting nanopapers exhibited a tensile strength of ~ 17 MPa and a transmittance of 25%. These nanopapers present a viable pathway toward eco-friendly products in various industries, promising to revolutionize upcoming sustainable packaging technologies.